2015
DOI: 10.1007/s11255-014-0903-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and outcome analysis of adult lupus nephritis patients in China

Abstract: Clinicopathological characteristics, treatment responses and long-term outcomes differ remarkably in LN patients with different gender and pathological subtypes. New indicators of poor renal outcome were identified. Infections and TTP were the most common causes of death in LN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 25 publications
6
32
0
4
Order By: Relevance
“…Hypertension, serum creatinine level, hypocomplementemia, renal proliferative lesion, SLEDAI score, age, male gender, and proteinuria were identified as independent risk factors for poor prognosis of LN patients in different studies. [ 8 10 ] In the present study, we found that several clinical indexes, that is, nephrotic syndrome and low eGFR at diagnosis, were also risk predicting factors. These findings were consistent with results from observational studies.…”
Section: Discussionsupporting
confidence: 57%
“…Hypertension, serum creatinine level, hypocomplementemia, renal proliferative lesion, SLEDAI score, age, male gender, and proteinuria were identified as independent risk factors for poor prognosis of LN patients in different studies. [ 8 10 ] In the present study, we found that several clinical indexes, that is, nephrotic syndrome and low eGFR at diagnosis, were also risk predicting factors. These findings were consistent with results from observational studies.…”
Section: Discussionsupporting
confidence: 57%
“…Lupus nephritis-IV (DPLN) is the most common, severe, and active form of nephritis; the prognosis of these classes of patient is directly proportional to the period of diagnosis and initiation of effective therapy [ 3 , 4 ]. A recent large clinical study of LN has suggested that patients with LN-II and LN-III classes have favorable outcome whereas patients with LN-IV, LN-V, and LN-VI have poorer outcomes [ 5 ], which further emphasizes that early detection of active forms of LN is valuable fortitude to decrease the morbidity and mortality. Presently, renal biopsy provides information on the level of renal tissue injury, pathological activity, and severity of renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Table ( 8) shows rates of response between males and females with no significant difference; however despite being non significant our male patients showed a higher response rate either CR or PR than females.…”
Section: Results:-mentioning
confidence: 59%